ANALISIS KINERJA APOTEK AVICENA MENGGUNAKAN PENDEKATAN BALANCED SCORECARD DENGAN ANALISIS SWOT - Eka Hayati Rhomah; Titik Sunarni; Ika Purwidyaningrum (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
The concept of BSC can be used as performance evaluation tool . The purpose of this study is to analyze the performance of Pharmacy in BSC perspectives and determine the strategic map using SWOT method. This research is non-experimental research with a descriptive design. Performance on the BSC. The results of performance measurements are combined with SWOT analysis to determine the strategy map. The results showed the value of TOR, ROI and Nett Profit Margin have not met the standard. Dispensing time meets the standards; Based on the SWOT analysis, the strategy map prepared prioritizes strengthening perspective of learning and growth to improve the quality of pharmaceutical services so can increase customer and revenue growth.